ANALISIS KEMAMPUAN MEMBAYAR PINJAMAN OLEH PETANI PADA EKS PROYEK UPP PERKEBUNAN TREE CROPS SMALLHOLDER DEVELOPMENT PROJECT (TCSDP) - Syaiful Hadi; Ahmad Rifai (Fakultas Pertanian, Universitas Riau, 2014)
Rubber plantation development program pattern Project Implementation Unit (UPP) is Develompment Smallholder Tree Crops Project (TCSDP) which is a rubber plantation development program to combine the management with regard to technology, production and marketing process financed by Dunia.Penelitian Bank aims to analyze revenue , spending and ability to pay credit ex TCSDP rubber farmers. Results of the study found that the productivity of the former rubber plantation TCSDP almost reached the target KKK 1,500 kg / hectare / tahun.Pendapatan rubber farmers from the former rubber plantation TCSDP has contributed substantially to the income of farm households peserta.Pengeluaran non-food household rubber farmers ex TCSDP two-thirds of food expenditure and relatively prosperous. Farmers ex TCSDP very able to pay the mortgage loan repayment rate kredit.Rendahnya more due to management are not well established